# lim-x-3-cos-3pi-2x-x-3-

Question Number 134378 by mohammad17 last updated on 02/Mar/21
$${lim}_{{x}\rightarrow\mathrm{3}} \frac{{cos}\left(\frac{\mathrm{3}\pi}{\mathrm{2}{x}}\right)}{{x}−\mathrm{3}} \\$$
Answered by bramlexs22 last updated on 02/Mar/21
$$\underset{{x}−\mathrm{3}\rightarrow\mathrm{0}} {\mathrm{lim}}\:\frac{\mathrm{cos}\:\left(\frac{\mathrm{3}\pi}{\mathrm{2x}}\right)}{\mathrm{x}−\mathrm{3}} \\$$$$\mathrm{let}\:\mathrm{x}−\mathrm{3}=\mathrm{w}\:\Rightarrow\:\frac{\mathrm{1}}{\mathrm{x}}=\frac{\mathrm{1}}{\mathrm{w}+\mathrm{3}} \\$$$$\underset{\mathrm{w}\rightarrow\mathrm{0}} {\mathrm{lim}}\:\frac{\mathrm{cos}\:\left(\frac{\mathrm{3}\pi}{\mathrm{2}\left(\mathrm{w}+\mathrm{3}\right)}\right)}{\mathrm{w}}\:= \\$$$$\underset{\mathrm{w}\rightarrow\mathrm{0}} {\mathrm{lim}}\:\frac{\frac{\mathrm{3}\pi}{\mathrm{2}\left(\mathrm{w}+\mathrm{3}\right)^{\mathrm{2}} }.\mathrm{sin}\:\left(\frac{\mathrm{3}\pi}{\mathrm{2}\left(\mathrm{w}+\mathrm{3}\right)}\right)}{\mathrm{1}}\:=\:\frac{\pi}{\mathrm{6}} \\$$
Commented by mr W last updated on 03/Mar/21
$$\frac{\mathrm{3}\pi}{\mathrm{2}}×\frac{\mathrm{1}}{\mathrm{3}^{\mathrm{2}} } \\$$
Commented by bramlexs22 last updated on 02/Mar/21
$$\frac{\mathrm{d}}{\mathrm{dw}}\:\left[\mathrm{cos}\:\left(\frac{\mathrm{3}\pi}{\mathrm{2}\left(\mathrm{w}+\mathrm{3}\right)}\right)\right]= \\$$$$\frac{\mathrm{d}}{\mathrm{dw}}\:\left[\mathrm{cos}\:\frac{\mathrm{3}\pi}{\mathrm{2}}\left(\mathrm{w}+\mathrm{3}\right)^{−\mathrm{1}} \:\right]= \\$$$$−\frac{\mathrm{3}\pi}{\mathrm{2}}.\left(\mathrm{w}+\mathrm{3}\right)^{−\mathrm{2}} \:\left[−\mathrm{sin}\:\left(\frac{\mathrm{3}\pi}{\mathrm{2}\left(\mathrm{w}+\mathrm{3}\right)}\right)\right] \\$$$$\underset{\mathrm{w}\rightarrow\mathrm{0}} {\mathrm{lim}}\:\:\frac{\mathrm{3}\pi}{\mathrm{2}\left(\mathrm{w}+\mathrm{3}\right)^{\mathrm{2}} }.\mathrm{sin}\:\left(\frac{\mathrm{3}\pi}{\mathrm{2}\left(\mathrm{w}+\mathrm{3}\right)}\right)= \\$$$$\frac{\mathrm{3}\pi}{\mathrm{18}}×\mathrm{1}=\frac{\pi}{\mathrm{6}} \\$$
Answered by mathmax by abdo last updated on 02/Mar/21
$$\mathrm{f}\left(\mathrm{x}\right)=\frac{\mathrm{cos}\left(\frac{\mathrm{3}\pi}{\mathrm{2x}}\right)}{\mathrm{x}−\mathrm{3}}\:\:\mathrm{changement}\:\frac{\mathrm{3}\pi}{\mathrm{2x}}=\frac{\pi}{\mathrm{2}}+\mathrm{t} \\$$$$\mathrm{x}\rightarrow\mathrm{3}\:\Rightarrow\mathrm{t}\rightarrow\mathrm{0}\:\mathrm{and}\:\frac{\mathrm{3}\pi}{\mathrm{2x}}=\frac{\mathrm{2t}+\pi}{\mathrm{2}}\:\Rightarrow\frac{\mathrm{3}\pi}{\mathrm{x}}=\mathrm{2t}+\pi\:\Rightarrow\frac{\mathrm{x}}{\mathrm{3}\pi}=\frac{\mathrm{1}}{\mathrm{2t}+\pi}\:\Rightarrow \\$$$$\mathrm{x}=\frac{\mathrm{3}\pi}{\mathrm{2t}+\pi}\:\Rightarrow\mathrm{x}−\mathrm{3}=\frac{\mathrm{3}\pi}{\mathrm{2t}+\pi}−\mathrm{3}\:=\frac{\mathrm{3}\pi−\mathrm{6t}−\mathrm{3}\pi}{\mathrm{2t}+\pi}\:=\frac{−\mathrm{6t}}{\mathrm{2t}+\pi}\:\Rightarrow \\$$$$\mathrm{f}\left(\mathrm{x}\right)=\mathrm{g}\left(\mathrm{t}\right)=\frac{\mathrm{cos}\left(\frac{\pi}{\mathrm{2}}+\mathrm{t}\right)}{\frac{−\mathrm{6t}}{\mathrm{2t}+\pi}}\:=\frac{\left(\mathrm{2t}+\pi\right)\mathrm{sint}}{\mathrm{6t}}\:\Rightarrow\mathrm{g}\left(\mathrm{t}\right)\sim\frac{\mathrm{2t}+\pi}{\mathrm{6}}\:\rightarrow\frac{\pi}{\mathrm{6}}\:\Rightarrow \\$$$$\mathrm{lim}_{\mathrm{x}\rightarrow\mathrm{3}} \mathrm{f}\left(\mathrm{x}\right)=\frac{\pi}{\mathrm{6}} \\$$$$\\$$